Modulation of Astrocytic Glutamine Synthetase by Endocannabinoid 2-Arachidonoylglycerol in JNK-Independent Pathway - Wang, Jing; Wang, Shenghong; Zhang, Hua (Frontiers in Pain Research, 2021)
Background and objective: The glutamine synthetase (GS), an astrocyte-specific enzyme, plays an important role in neuroprotection through the glutamate/glutamine shutter and can be modulated by endocannabinoid 2-arachidonylglycerol (2-AG) through ERK1/2 and p38 signaling pathways. However, the role of JNK signaling pathway in the modulation of GS in astrocytes by 2-AG is not clear. Material and methods: The expression of GS and JNK in astrocytes following lipopolysaccharide (LPS)-exposure was examined with western blotting and immunochemistry. Results: The results revealed that short-term exposure of LPS activated GS and increased phosphorylation of JNK in astrocytes in time-dependent manner. Treatment with 2-AG reversed the changes of GS but had no effect on JNK activation. Conclusion: These findings suggest that the activation of JNK induced by LPS is not involved in the modulation of astrocytic GS by 2-AG.